Efficacy of Topical Cyclosporine 0.05% in the Treatment of Meibomian Gland Dysfunction: A Hospital Based Prospective Study - Shrestha, Poonam; Kaini, Khem Raj; Shrestha, Tirtha Man (Journal of Karnali Academy of Health Sciences, 2019)
Purpose: To compare the efficacy of topical cyclosporine 0.05% with tobramycin 0.3% and dexamethasone 0.1% eye drop in reducing signs and symptoms of Meibomian gland dysfunction. Design: A hospital based randomized prospective study conducted at Manipal Teaching Hospital, Department of Ophthalmology, Pokhara, over a period of 18 months, from January 2012 to June 2013. Methods: 30 patients who were diagnosed as Meibomian gland dysfunction were recruited and randomly assigned into two groups i.e. Group- A received Cyclosporine 0.05% and Group-B received Tobramycin/dexamethasone. Before starting treatment ocular symptoms were recorded with help of OSDI score. All patients underwent examinations including visual acuity, intraocular pressure, Schirmer’s test, Tear break up time, Lissamine staining, slit lamp examination for lid telangiectasia, open and clogged meibomian glands, inclusions and meibomian secretion quality. Result: OSDI score significantly improved in cyclosporine group than in tobramycin/dexamethasone group. Other objective measurements like Schirmer value, Lissamine staining, meibomian secretion quality, number of lid telangiectasia and clogged glands improved in Cyclosporine group. Conclusion: The present hospital based study noted that Meibomian gland dysfunction can be more effectively treated with cyclosporine than tobramycin/dexamethasone.